2014
DOI: 10.1016/j.cogdev.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of search speed in the contextual cueing of children's attention

Abstract: The contextual cueing effect is a robust phenomenon in which repeated exposure to the same arrangement of random elements guides attention to relevant information by constraining search. The effect is measured using an object search task in which a target (e.g., the letter T) is located within repeated or nonrepeated visual contexts (e.g., configurations of the letter L). Decreasing response times for the repeated configurations indicates that contextual information has facilitated search. Although the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Despite apparent contradictions, this literature leads to the conclusion that the MTL plays a crucial role in implicit CC and that, although not required, the hippocampus might also be engaged even when knowledge remains implicit [16]. In concordance, while some research has shown that CC matures early in childhood [40] and is spared during aging [41], other studies suggest that particular processes engaged in CC might follow a pattern of ontogenetic maturation and age-related decline more similar to those usually associated with explicit memory [21,[42][43][44][45]. Although seemingly contradictory, diverging results reported in the literature can nonetheless be explained by the variety of mechanisms involved in CC and by the fact that different SL phenomena may be revealed by the CC phenomenon.…”
Section: Reviewmentioning
confidence: 90%
“…Despite apparent contradictions, this literature leads to the conclusion that the MTL plays a crucial role in implicit CC and that, although not required, the hippocampus might also be engaged even when knowledge remains implicit [16]. In concordance, while some research has shown that CC matures early in childhood [40] and is spared during aging [41], other studies suggest that particular processes engaged in CC might follow a pattern of ontogenetic maturation and age-related decline more similar to those usually associated with explicit memory [21,[42][43][44][45]. Although seemingly contradictory, diverging results reported in the literature can nonetheless be explained by the variety of mechanisms involved in CC and by the fact that different SL phenomena may be revealed by the CC phenomenon.…”
Section: Reviewmentioning
confidence: 90%
“…This finding suggests that CC can be observed across different levels of task difficulty and is in line with the finding that “what” and “where” learning facilitates search regardless of memory load (Makovski, ). Together, these data suggest that although CC is specific, it is nevertheless robust and it is not modulated by the ease of processing or overall RT (Darby, Burling, & Yoshida, ).…”
Section: Discussionmentioning
confidence: 85%
“…The idea that objects from the same category often share both conceptual and perceptual commonalities is not a novel one; in fact, it underlies earlier proposals about the relevancy of competition and contrast in early word learning (Klibanoff and Waxman 2000;Mandler and Hall 2002;Mandler 2000;Eimas and Quinn 1994;Yoshida and Hanania 2013). However, the idea of commonalities also fits what is known about how attention is flexibly cued by past learning (Kruschke 1996(Kruschke , 2009Chun and Jiang 1998;Darby et al 2014;Burling and Yoshida 2016) and how the learned attentional shifts can reduce memory interference and improve word learning (Merriman 1999;Smith et al 2002;Smith 2005;Smith 2005, Yoshida andBurling 2012).…”
Section: Introductionmentioning
confidence: 81%